Tools of Radio Astronomy - Problems and Solutions - Wilson, T.L (Astronomy and Astrophysics Library,, 2018)
Covering topics of radio astronomy, this book contains graduate-level problems with carefully presented solutions. The problems are arranged following the content of the book "Tools of Radio Astronomy, 6th Ed." by T.L.Wilson, K. Rohlfs, S. Hüttemeister (also available in the this series) on a chapter-by-chapter basis. Some of these problems have been formulated to provide an extension to the material presented in "Tools of Radio Astronomy".